[Just once ; Brother right or wrong; Bringing back EDSA [videorecording] - Lazaro, Cheche (The Probe Team ; episode no.140., 1991)
James Ingram concert in the Philippines and his well loved music; the death of Lenny Villa during a fraternity initiation; Anniversary of the EDSA revolution.